TRANSFORMASI PENGATURAN TINDAK PIDANA PERZINAAN DALAM PERSPEKTIF PEMBARUAN HUKUM PIDANA INDONESIA - Mutiara Putri Nirwanawati (Jurnal Ilmiah Advokasi, 2026)
This article examines the implications of the revised Indonesian Criminal Code (Law No. 1/2023) on privacy rights and legal certainty. Using normative legal research and doctrinal analysis of statutory texts, regional regulations, and relevant court decisions, the study finds that recasting zina as a complaint-based offense and retaining vague statutory language narrows the scope of criminalization while simultaneously increasing the risk of privacy intrusions and legal uncertainty. Divergences between national provisions and customary norms across several regions further create opportunities for inconsistent interpretation and discriminatory application. These findings directly address the study objective by showing how both substantive and procedural changes affect the two focal dimensions. The study underscores the need for harmonization of legal norms and stronger safeguards for individual rights.Keywords: Adultery; Customary Law; National Law; Criminal Law Reform